Wideband DB-linear VGA for high-speed communications - Kong, Lingshan (2019)
In this thesis, novel ideas are proposed to extend the gain range effectively with minimum hardware. Firstly, the approach by tuning the transconductance and output resistance of the amplifier simultaneously is brought forward. Secondly, a new constructing method to improve the gain range is presented by exploiting the convex and concave functions together. With the proposed methods, a wideband VGA for wireless communication and a 10 Gb/s AGC system for wireline communication are designed, respectively. Broadband techniques are adopted in order to achieve an inductorless design while minimizing the chip area. Both of them are fabricated with 65 nm CMOS process and demonstrate a competitive performance compared with the state-of-the-art works. With the help of proposed exponential realization methods, VGA and AGC with large gain range, wide bandwidth while low power consumption are achieved.